Oscillation theorems for nonlinear fractional difference equations - Hakan Adiguzel (Boundary Value Problems, 2018)
Abstract In this study, we discuss some theorems related to the oscillatory behavior of nonlinear fractional difference equations equipped with well-known fractional Riemann–Liouville difference operator. Then we give an example for the illustration of the results obtained.